Dampak Jumlah Anggota Keluarga dan Pendidikan terhadap Pola Konsumsi Rumah Tangga Miskin - Sri Nadia; Mustofa Umar; Juardi (Bulletin of Economic Studies (BEST), 2022)
This study aims to determine the effect of the number of family members and education on the consumption patterns of poor households in Lembang District, Pinrang Regency. The type of research used is quantitative research with an explanatory approach. The data used in this study are secondary data and primary data with a total of 30 respondents. The research technique used is documentation and semi-structured interviews related to this research. The test was carried out using multiple linear regression analysis using SPSS version 25 software. The conclusion obtained in this study is that the number of family members has a positive and significant effect on the consumption pattern of poor households. Education has no significant effect on the consumption pattern of poor households. However, simultaneously the number of family members and education have a significant effect on the consumption patterns of poor households.